"It's Hard to Be Around Here": Criminalization of Daily Routines for Youth in Baltimore. (January 2019) - Boyd, Melody L.; Clampet-Lundquist, Susan
The authors examine how youth in Baltimore experience criminalization in their everyday routines in two key social settings, schools and neighborhoods, and how this can affect their transition to adulthood. Respondents are African Americans between the ages of 15 and 24 who have spent some of their childhood in Baltimore's poorest neighborhoods. The authors conducted qualitative, semistructured, in-depth interviews with 150 respondents. Many of the daily routines of low-income young African Americans are shaped by a punitive culture of formal social control that often results in exposure to microaggressions, which can act as a chronic stressor and negatively affect the transition to adulthood. This analysis adds to our understanding of how daily routines influence the activities, perceptions, and transitions to adulthood of youth who have grown up in poor neighborhoods.